ACTIVATING ISLAMIC CULTURAL HISTORY LEARNING THROUGH DOCUMENTARY FILMS IN CLASS VIII MTs ZIA SALSABILA - Amalia Nurhanisah Gultom; Zulham (International Journal of Cultural and Social Science, 2025)
This study aims to activate the learning of Islamic Cultural History (SKI) through the use of documentary films in the eighth-grade class at MTs Zia Salsabila. The background of this research is the low interest and participation of students in SKI learning, which tends to be monotonous and dominated by lecture-based methods. This study employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation involving teachers, students, and the vice principal. The findings indicate that the use of documentary films has a positive impact on student engagement, material comprehension, and the quality of classroom interaction. Students became more enthusiastic, actively participated in discussions, and found it easier to understand historical contexts through the visualization of events and figures. Documentary films serve not only as a learning aid but also as a strategic approach that aligns with the characteristics of 21st-century learners. With proper teacher guidance, this medium has proven effective in creating contextual, enjoyable, and meaningful learning experiences.